Timaeus - Plato, 428? BCE-348? BCE; Jowett, Benjamin, 1817-1893 (Salt Lake City, UT : Project Gutenberg, 1998)
"Timaeus" by Plato is a philosophical dialogue written around 360 BC. Through lengthy monologues, the work explores the nature of the physical universe and humanity's place within it. A divine craftsman$1 (Bthe demiurge$1 (Bbrings order from chaos, shaping the cosmos according to eternal, perfect forms. The dialogue examines why the world exists as a living, intelligent whole and how the elements were organized from primordial disorder. It also references the legendary tale of Atlantis, setting the stage for deeper cosmological speculation. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Timaeus_(dialogue)
Release date is 1998-12-01
Sue Asscher and David Widger
Keywords: Classical literature; Cosmology -- Early works to 1800